Buy or Bye: Exploring The Trigger of Impulse Buying Behavior Among Gen Z in Lifestyle Retail - Maula, The Syifaul; Kurniati, Rini Rahayu; Deka, Rio Era (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: In today's competitive retail business, many stores, including KKV, are implementing innovative marketing strategies to attract customers, especially Generation Z. However, this generation is known to be more critical and selective in shopping, including in making impulse buying.Purpose: This study explores the influence of product assortment and store atmosphere on impulse buying with hedonic shopping motivation as an intervening variable at KKV outlets.Design/Methodology/approach: This research uses an explanatory research approach. The study's population consisted of all customers, including Generation Z, who had shopped at KKV Mall Olympic Garden Malang City. The sample was selected by purposive sampling of 100 respondents. The Structural Equation Modeling (SEM) techniques were used to analyze data collected through questionnaires.Finding/Result: The results showed that product assortment and store atmosphere positively and significantly influence hedonic shopping motivation. However, these two variables do not directly affect impulse buying. Hedonic shopping motivation is shown to have a positive and significant influence on impulse buying and can function as a mediator between product assortment and impulse buying, but the relationship between store atmosphere and impulse buying cannot be mediated by it.Conclusion: This research provides practical, useful information to retailers on creating more successful marketing campaigns to encourage impulse buying behavior in Generation Z and opens up opportunities for further research on other factors that can influence consumer purchasing decisions in the retail environment. Originality/value (State of the art): This research fills the literature gap by exploring the role of hedonic shopping motivation as a mediator between external stimuli and impulse buying. Previous research has rarely addressed this topic, thus providing significant managerial implications and a valuable contribution to understanding consumer behavior. Keywords: hedonic shopping motivation, impulse buying, product assortment, store atmosphere